Intravascular Papillary Endothelial Hyperplasia as a Cause of Reversible Vision Loss. Issue 3 (May 2021) - Liu, Catherine; Daigle, Patrick; Munoz, David G.; Nijhawan, Navdeep
Abstract : Abstract: Intravascular papillary endothelial hyperplasia (IPEH) is a benign vascular lesion that is formally diagnosed on histopathology. IPEH seldom presents in periocular tissues and is even less commonly seen deep within the orbit. As with cavernous hemangioma, this lesion tends to distort surrounding structures and can cause a significant mass effect in the orbit. The authors present an unusual case of orbital IPEH that resulted in severe proptosis and progressive vision loss from optic nerve compression. In toto surgical excision of the lesion resulted in significant recovery of vision loss and resolution of symptoms associated with proptosis. To the best of our knowledge, this case is the first to illustrate the potential for visual recovery after surgery in a patient with compressive optic neuropathy from orbital IPEH.